The Effect of Comic Strips and Motivation on the Senior High School Students’ Speaking Ability - Zul Amri; Rusdi Noor Rosa; Helvi Yosi (Fakultas Bahasa dan Seni UNP, 2023)
Considering the importance of speaking ability for senior high school students in learning English as a foreign language, researchers continue developing approaches, methods, and media in teaching speaking. One of the media that can be used in teaching speaking English is comic strips. This study aimed to find out whether using comic strips and motivation have an effect on the speaking ability of the tenth grade senior high students at SMA Adabiah 2 Padang. This study was conducted using an experimental method with factorial design 2x2. The population of the study was the tenth grade students at SMA Adabiah 2 Padang in the academic year 2021/2022. The total number of the population was 113 students, distributing in four classes. The sample was chosen using a cluster random sampling technique. The sample was Class X-2 as the control class (30 students) and Class X-3 as the experimental class (29 students). The data were obtained from the motivation questionnaire and speaking test. Then the data were analyzed using t-test and 2-way ANOVA. The results indicated that using comic strips and motivation had a significant effect on the students’ speaking ability. In conclusion, comic strips are a helpful media in teaching speaking English to senior high school students.